Profiling Creative Thinking Skills among Elementary School Students: A Study Based on the Merdeka Curriculum Elements - Jumanto; Sa’ud, Udin Syaefudin; Sopandi, Wahyu (Universitas Veteran Bangun Nusantara, 2024)
The creative thinking skills of students have become one of the focuses currently being pursued for improvement in Indonesia. This is manifested by incorporating creative thinking skills as one of the characters to be trained in the Merdeka Curriculum. This research aims to determine the profile of creative thinking skills of elementary school students in Surakarta city, thus providing considerations for the implementation and evaluation of the Merdeka Curriculum. The research was conducted using a survey method. The sample consisted of 200 fourth-grade students from 9 elementary schools in 5 districts of Surakarta city. There were 106 (53%) female and 94 (47%) male students in the sample. Sample selection was done using purposive sampling, by selecting fourth-grade classes as they have been implementing the Merdeka Curriculum for 2 years. The instrument used was a case-based essay test. The questions referred to the elements and sub-elements of creative thinking skills from the regulations governing the Profil Pelajar Pancasila of the Merdeka Curriculum. The data were analyzed descriptively quantitatively. The research findings indicate that the creative thinking skills of elementary school students in Surakarta City are still relatively low, with an average score of 49.87. The implementation of the Merdeka curriculum, which focuses on 6 dimensions of student character, one of which is creative thinking, has not yet been able to enhance students' creative thinking skills.